The Effect of the SAMRY Model (Mahfudzat Adaptation Stress and Guided Imagery) on Nurse Work Stress - Kurniawati, Ayu Khuzaimah; Pramana, Cipta; Pohan, Vivi Yosafianti; Hartiti, Tri; Soesanto, Edy; Astuti, Rahayu (Jurnal Kesehatan Masyarakat, 2024)
Nurses’ work stress must be managed well. Work stress can affect nurses’ performance, reduce service quality, and cause turnover intention. The 2018 PPNI survey showed that 50.9% of Indonesian nurses experienced work stress. A preliminary study at K.R.M.T Wongsonegoro Hospital Semarang of 10 nurses in special units stated that 90% experienced work stress. The SAMRY (Stress Adaptation and Guided Imagery) model can reduce nurses’ work stress. This technique combines the application of the concepts of mahfudzat and guided imagery so that it can create relaxation distractions and increase adaptive coping patterns. This research aims to determine the effect of the SAMRY model on nurses’ work stress. The research method uses a pre-experiment with a pre-post-test one-group design. The population is 223 nurses who work in special units. Sample of 35 respondents using a purposive random sampling technique. Data collection was carried out by assessing work stress pre and post-intervention. The research instrument used the Expanded Nursing Stress Scale (ENSS) questionnaire. The results of the study reported an average pre-intervention work stress score of 114 and post-intervention 78.26. Data analysis using the paired sample t-test obtained p-value=0.000 (p0.05). It can be concluded that there is an influence of the SAMRY model on nurses’ work stress.